Myth busters: centring disability and displacing ableism through reimagining dissertation mentoring with care and critical pedagogy - Leigh Graves Wolf; Jacob C. Bunch (Journal of Learning Development in Higher Education)
This brief communication is the account of an emancipatory learning journey between a doctoral dissertationwriter and supervisor. In the spring of 2022, we started down a path of pushing boundaries and working through normative expectations and perceived rigidities of qualitative research. Coming from the perspectives of a disabled, first-generation doctoral researcher with Cerebral Palsy and multiple learning disabilities, and a first-generation faculty member with a chronic disease (endometriosis), this opinion piece will invite readers into a conversation which explains how the experience of the dissertation mentoring process raised our consciousness of educational trauma, ableism, and its intersection with knowledge production, specifically in the realm of qualitative inquiry. We will explore how caring and critical pedagogies supported the development of a genre-busting dissertation, which heavily integrated multimodal explorations to examine assistive technology lifeworlds from the perspective of postsecondary students with dyslexia. Through the dissertation analysis, innovative and inclusive qualitative methodological processes were developed. By rooting the experiences in care, both researcher and supervisor found joy through a process which can often be isolating, especially in an entirely online modality. At the core, the brief conversation presented explores: how did the innovations that came from the experience emancipate and restore the researcher, co-partners, and guiding faculty?